Penetration testing essentials - Oriyano, Sean-Philip (Indianapolis, Indiana : Sybex, a Wiley brand, 2017)
IT Security certifications have stringent requirements and demand a complex body of knowledge. This essential guide lays the groundwork for any IT professional hoping to move into a cybersecurity career by developing a robust pen tester skill set. --
Includes index.
Description based on print version record.
Keywords: Penetration testing (Computer security); Hackers; Computer crimes -- Prevention; Computer crimes -- Prevention; Hackers; Penetration testing (Computer security); Electronic books